A systematic review of nomograms used in urolithiasis practice to predict clinical outcomes in paediatric patients. Issue 4 (August 2022) - Kailavasan, Mithun; Berridge, Christopher; Yuan, Yuhong; Turner, Alexander; Donaldson, James; Biyani, Chandra Shekhar
Summary: Introduction: Nomograms, used to predict the risk and success of treatment of urinary tract stones, are being used in paediatric clinical practice. However, no studies have determined the best prediction model. This study aimed to identify the most robust nomogram(s) for predicting clinically relevant outcomes in urinary stone disease in paediatric patients. Methods: The EMBASE, MEDLINE, Cochrane Systematic Reviews, and Cochrane Central Register of Controlled Trials via Ovid were searched for publications on May 13, 2021. No study design and publication year limitations were applied. The risk of bias in the included studies was determined using PROBAST. Results: The review included fourteen studies, involving 3888 paediatric patients. We identified seven prognostic stone nomograms (Dogan, Onal, CMUN, SKS, Guy's stone score, S.T.O.N.E and CROES) that were validated for use in paediatric patients. Both Dogan and Onal scores were developed and internally and externally validated in different studies with similar AUC scores between 0.6 and 0.7. For PCNL practice, two nomograms were developed and internally validated (CMUN, SKS) but not externally validated. The Guy's stone score was found to have the lowest overall accuracy in predicting stone-free rates in the externally validated nomograms studies. Nine of the fourteen studies included were judged as having a high risk of bias in their overall judgement. Conclusion: The systematic review findings should be interpreted with caution given the heterogeneity of included studies. There is no difference between the use of the Dogan or Onal score for predicting outcomes associated with ESWL. For predicting outcomes of PCNL, CROES had the greatest supportive evidence, whilst the SKS or CMUN scores lack external validation and require further evaluation to assess their utility in predicting PCNL outcomes.